MEDIA X-RECORDER DAN YOUTUBE UNTUK MENINGKATKAN MOTIVASI BELAJAR BAHASA INDONESIA MODA DARING - Imro'atus Sholihah (El-Tsaqafah : Jurnal Jurusan PBA, 2022)
This study describes the use of X-Recorder and Youtube media applications and explains how the effectiveness of using X-Recorder and Youtube media in increasing student motivation in learning Indonesian at MTsN 4 Jombang. The research method used is descriptive qualitative. This research was conducted on class VII students of MTsN 4 Jombang. The research was conducted for two cycles with several stages which included planning, implementing actions, observing activities, and reflecting. Based on the results of the research, the enthusiasm of students in carrying out online learning has increased significantly so that it can be said that the application of X-Recorder and Youtube media can increase student motivation because students can feel the presence and guidance of the teacher so that learning is more directed and meaningful. This research concludes that the application of X-Recorder and Youtube media can increase students' learning motivation at MTs.Negeri 4 Jombang. Student learning outcomes are strongly influenced by the quality of learning implemented in madrasas. One that determines the quality of learning is the use of appropriate learning media and also the presence of a teacher. One of the learning media that can be applied to online learning is the X-Recorder and Youtube media